Effects of biofeedback game on affects and anxiety among undergraduate students - Ling, Gong Shuen; Ng, Kuan Sien; Tan, Pei Chin (2020)
This study aimed to investigate the effects of biofeedback game on affection and anxiety among undergraduate students. This study was conducted in an experimental study with pilot randomized controlled trial (RCT) design by using purposive sampling method. The participants are 28 undergraduate students in UTAR who aged from 18 to 22 years old with a mean age of 22 years old (SD = 1.14 for intervention group, SD = 1.33 for control group). The demographic questionnaire was given as serving for quantitative survey. Positive and Negative Affect Schedule (PANAS), State-Trait Anxiety Inventory (STAI) are used to measure the variables in this study. The result revealed that there is a significant difference of the heart rate variability between treatment and the control group at post-test. All of the variables have significant differences between pre and post-test, except for positive affection. The limitation and recommendation of present study are discussed. In conclusion, the present study found little evidence on the effects of biofeedback games in reducing negative affection, anxiety, and improving positive affection.